The kinship greetings of blood and marital ties in the Minangkabau community: A sociolinguistic study - Salliyanti, Salliyanti; Susiolo, Hariadi; Kudadiri, Amhar (Linguistics and Culture Review, 2021)
This study aimed to explore the use of regional languages regarding forms of kinship based on blood and marital ties greetings by the Minangkabau's in the Bromo area. To analyze the forms of blood and marriage-related kinship greetings, a sociolinguistic study was applied. The data collection was listening to the informants' conversation regarding greetings for the Minangkabau community, followed by talking engaging techniques. The analyzed using the equivalent method with the qualitative approach. The results showed that form of blood kinship greeting such as Apak, Amak, Uda, Uni, Adiak, Anduang, Mak Gaek, Angku, Ungku, Pak Gaek, Mak Dang, Mak Wo, Mak Etek, Etek, Apak, Andeh, and Pak Etek. There are several types such as Uda, Ajo, Adiak, Abak, Amak, Uda, Ajo, Uni for marital ties greetings. These greetings, both blood, and marital kinship ties indicate cultural resistance and social bonding, which have roles in daily communication among the Minangkabau people.